Lettered Christians : Christians, letters, and late antique Oxyrhynchus - Blumell, Lincoln H. (Lincoln Harris), 1975- (New Testament tools, studies and documents, 2012)
This book offers a detailed survey of the surviving Christian letters from Oxyrhynchus, which up until this time have never been collectively examined, and shows how this unique body of evidence can be used to elucidate a number of issues relating not only to Christianity in the Oxyrhynchite but also larger Christianity in late antique Egypt.